Risk factors for target vessel endoleaks after physician-modified fenestrated or branched endovascular aortic arch repair: A retrospective study - Chen, Zhipeng; Fu, Dongsheng; Liu, Cheng; Jin, Yi; Pan, Chaohui; Mamateli, Subinur; Lv, Xiaochen; Qiao, Tong; Liu, Zhao (Frontiers in Cardiovascular Medicine, 2023)
Objective: Fenestrated or branched endovascular aortic arch repair (fb-arch repair) is an effective option for treating complex aortic arch lesions, including thoracic aortic aneurysms and aortic dissections. However, the relatively high rate of re-intervention due to target vessel (TV)-related endoleaks have raised concerns. This study aimed to determine risk factors for TV-related endoleaks after fb-arch repair. Methods: This was a retrospective analysis of all patients undergoing fb-arch repair between 2017 and 2021in nanjing. All the patients underwent computed tomography angiography (CTA) before surgery; at discharge; and at 3 months, 6 months, and yearly post-discharge. Two experienced vascular surgeons used CTA and vascular angiography data to assess endoleaks. The study endpoint was emergence of and re-intervention for TV-related endoleaks. Results: Among the 198 patients considered (mean age, 59 ± 13.3 years; 85% male), 309 branch arteries were revascularized. A total of 35 TV-related endoleaks were identified in 28 patients during a mean follow-up of 23 ± 14 months: six type Ic, 4 type IIIb, and 20 type IIIc endoleaks. Patients in the endoleak group had greater aortic arch segment diameters (43.1 ± 5.1 versus 40.3 ± 4.7; P = 0.004) and a greater number of TVs revascularized (2.0 ± 0.8 versus 1.5 ± 0.8; P = 0.004) than those in the non-endoleak group. However, the morphological classification of the aortic arch did not seem to affect the occurrence of TV endoleaks (13%, 14%, and 15% for type І, II, and III aortic arches, respectively; P = 0.957). Pre-sewing branch stents in the fenestration position reduced the risk of TV endoleaks (5% versus 14%; P = 0.037). Additionally, in TVs affected by aortic aneurysm or dissection, the risk of endoleaks increased after reconstruction (17% versus 8%; P < 0.018). Conclusion: The data from this study showed that patients with a larger aortic arch diameter or more revascularized arteries during surgery were at increased risk TV-related endoleaks. Invasion of branched vessels by the false lumen or aneurysm sac increased the risk of endoleaks after reconstruction. Finally, prefabricated branch stents reduced risk of TV-related endoleaks.